Elemental distribution and Pb speciation in vegetable and cereal seeds during germination by micro X‐ray fluorescence and X‐ray absorption near‐edge structure. (2nd April 2019) - Luo, Liqiang; Shen, Yating; Ma, Yanhong; Fu, Chenfei; Liu, Jian; Zeng, Yuan
Abstract : The distribution of the chemical elements in plants is closely correlated with biological functions. Micro X‐ray fluorescence (μXRF) and X‐ray absorption near‐edge structure (XANES) spectrometry can be used to determine uptake, translocation, and accumulation of the elements in plants. In this research, μXRF and XANES were applied in studying distribution of the elements in the vegetable and cereal seeds during germination and the mobilization. It was found that (a) the distribution of the elements in the seeds was element specific; (b) K and Ca were mainly located in the embryo. Fe and Zn, as well as Mn and Cu, concentrated near the radicle and new developed root. Most of Pb was located in the new developing root; (c) the organic‐Pb complexes functioned as the main components of translocation of Pb in the seeds during germination, and the formation of Pb5 (PO4 )3 Cl and Pb3 (PO4 )2 in seed and plant tissues was the mechanism of tolerance and detoxification to Pb in plants.